Bones : And the Stories They Tell - Naughton, Diane (NewYork Cambridge University, 2014)
Dinosaurs, Richard III, King Tut, the first humans to walk the earth$1! =(Bdiscover what we can learn about the past by studying bones. s
Cambridge Discovery Education Interactive Readers are the next generation of graded readers - captivating topics, high-impact video, and interactive exercises designed to motivate and engage.
Glossary, Contents.
Keywords: English language; Bones; Human skeleton; Pre-Intermediate Level